2017
DOI: 10.1038/srep40109
|View full text |Cite
|
Sign up to set email alerts
|

Computational and biochemical characterization of two partially overlapping interfaces and multiple weak-affinity K-Ras dimers

Abstract: Recent studies found that membrane-bound K-Ras dimers are important for biological function. However, the structure and thermodynamic stability of these complexes remained unknown because they are hard to probe by conventional approaches. Combining data from a wide range of computational and experimental approaches, here we describe the structure, dynamics, energetics and mechanism of assembly of multiple K-Ras dimers. Utilizing a range of techniques for the detection of reactive surfaces, protein-protein dock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
145
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(150 citation statements)
references
References 44 publications
5
145
0
Order By: Relevance
“…As shown, our chimeric BirA*Ras proteins were expressed as expected, localized as predicted, and their localization patterns matched the patterns of the proteins they biotinylated (Figures 1-4). K-Ras proteins also have been reported to oligomerize (17,20,(89)(90)(91), and we observed that WT, G12D, and S17N BirA*Ras proteins biotinylated WT pAMCherry1-KRas proteins in trans ( Figure 5). These results are of interest in the context of data that show both GDPbound and GTP-bound K-Ras proteins oligomerize in cells (20).…”
Section: Discussionmentioning
confidence: 59%
“…As shown, our chimeric BirA*Ras proteins were expressed as expected, localized as predicted, and their localization patterns matched the patterns of the proteins they biotinylated (Figures 1-4). K-Ras proteins also have been reported to oligomerize (17,20,(89)(90)(91), and we observed that WT, G12D, and S17N BirA*Ras proteins biotinylated WT pAMCherry1-KRas proteins in trans ( Figure 5). These results are of interest in the context of data that show both GDPbound and GTP-bound K-Ras proteins oligomerize in cells (20).…”
Section: Discussionmentioning
confidence: 59%
“…Diffusion of Ras is dominated by lateral mobility on the PM, 36,37 and we previously showed using EM and FLIM/FRET that clustering is decreased in the KE mutant and increased in CC relative to WT. 9 Together, these results suggest an altered molecular organization of KE and CC compared with WT. Consistent with this interpretation, the mobile fraction of molecular species is larger in KE (~89%) than WT and CC (73–76%).…”
Section: Resultsmentioning
confidence: 85%
“…9 To model larger K-Ras oligomers, we first required that each monomer within a cluster should bind a planar membrane. This eliminates oligomers of the D-symmetry group except D 2 (dimer of dimer).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) The proposed dimer interface with coordinating residues as obtained by MD simulations. A similar interface was proposed for K-Ras (Spencer-Smith et al, 2016;Prakash et al, 2017). Stephen et al, 2014;Chen et al, 2016;Lu et al, 2016), and elucidating the dimer interface at atomic detail will facilitate therapeutic approaches that modulate this interaction.…”
Section: Membrane Binding Of Rasmentioning
confidence: 68%